Qi-Dong-Huo-Xue-Yin Inhibits Inflammation in Acute Lung Injury in Mice via Toll-Like Receptor 4/Caveolin-1 Signaling. (11th February 2018) - Xu, Li-Ying; Cai, Wan-Ru; Ma, Chun-Fang; Shou, Qi-Yang; Qian, Jing-Li; Huseyin, Turan S.
Abstract : Acute lung injury (ALI) is a critical illness with no current effective treatment. Caveolin-1 indirectly activates inflammation-associated signaling pathways by inhibiting endothelial nitric oxide synthase (eNOS). This induces an imbalance between pro- and anti-inflammatory cytokine levels, which are involved in the pathogenesis of ALI. The compound Chinese prescription Qi-Dong-Huo-Xue-Yin (QDHXY) is efficacious for ALI treatment via an anti-inflammatory effect; however, the exact underlying mechanism is unknown. Therefore, we explored the protective effect of QDHXY against lipopolysaccharide- (LPS-) induced ALI in mice. Histopathological changes in mouse lung tissues were studied. Furthermore, alterations in the serum levels of pro- and anti-inflammatory cytokines were investigated. The levels of tumor necrosis factor- (TNF-) α, interleukin- (IL-) 6, IL-1 β, and interferon- γ -induced protein 10 in bronchoalveolar lavage fluid were measured. Additionally, the expression levels of myeloid differentiation factor 88 (MyD88), caveolin-1, and eNOS were assessed. QDHXY significantly reduced lung infiltration with inflammatory cells and the production of serum pro- and anti-inflammatory cytokines and inhibited the expression of TNF- α, IL-1 β, caveolin-1, and MyD88 but not eNOS. These indicate that QDHXY significantly improved the balance between pro- and anti-inflammatory cytokine levels, possibly by inhibiting the caveolin-1 signaling pathway. Therefore, QDHXY may be a potential treatment for ALI.